Splicing analysis of STAT3 tandem donor suggests non-canonical binding registers for U1 and U6 snRNAs - Kramárek, Michal; Souček, Přemysl; Réblová, Kamila; Grodecká, Lucie Kajan; Freiberger, Tomáš (Nucleic acids research, 2024)
Tandem donor splice sites (5'ss) are unique regions with at least two GU dinucleotides serving as splicing cleavage sites. The Δ3 tandem 5'ss are a specific subclass of 5'ss separated by 3 nucleotides which can affect protein function by inserting/deleting a single amino acid. One 5'ss is typically preferred, yet factors governing particular 5'ss choice are not fully understood. A highly conserved exon 21 of the STAT3 gene was chosen as a model to study Δ3 tandem 5'ss splicing mechanisms. Based on multiple lines of experimental evidence, endogenous U1 snRNA most likely binds only to the upstream 5'ss. However, the downstream 5'ss is used preferentially, and the splice site choice is not dependent on the exact U1 snRNA binding position. Downstream 5'ss usage was sensitive to exact nucleotide composition and dependent on the presence of downstream regulatory region. The downstream 5'ss usage could be best explained by two novel interactions with endogenous U6 snRNA. U6 snRNA enables the downstream 5'ss usage in STAT3 exon 21 by two mechanisms: (i) binding in a novel non-canonical register and (ii) establishing extended Watson-Crick base pairing with the downstream regulatory region. This study suggests that U6:5'ss interaction is more flexible than previously thought.
Keywords: RNA malá jaderná; vazba proteinů; RNA Splice Sites; sekvence nukleotidů; sestřih RNA; exony; Base Sequence; lidé; HeLa Cells; Binding Sites; místa sestřihu RNA; HeLa buňky; Humans; STAT3 Transcription Factor; Protein Binding; RNA Splicing; vazebná místa; transkripční faktor STAT3; RNA, Small Nuclear; Exons